The Molecular Chaperone CCT/TRiC: An Essential Component of Proteostasis and a Potential Modulator of Protein Aggregation - Grantham, Julie (Frontiers in Genetics, 2020)
Chaperonin containing tailless complex polypeptide 1 (CCT) or tailless complex polypeptide 1 ring complex (TRiC) is an essential eukaryotic molecular chaperone. It is a multi-subunit oligomer of two rings of eight individual protein subunits. When assembled, each of the eight CCT subunits occupies a specific position within each chaperonin ring. Thus a geometrically defined binding interface is formed from the divergent sequences within the CCT subunit substrate binding domains. CCT is required for the folding of the abundant cytoskeletal proteins actin and tubulin, which in turn form assemblies of microfilaments and microtubules. CCT is also involved in the folding of some additional protein substrates and some CCT subunits have been shown to have functions when monomeric. Since observations were made in worms over a decade ago using an RNAi screen, which connected CCT subunits to the aggregation of polyglutamine tracts, a role for CCT as a potential modulator of protein aggregation has started to emerge. Here there will be a focus on how mechanistically CCT may be able to achieve this and if this potential function of CCT provides any insights and directions for developing future treatments for protein aggregation driven neurodegenerative diseases generally, many of which are associated with aging.